End of Meeting Report - ISPC 10 - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2014)
The tenth ISPC meeting was attended by 45 participants from the 15th to the 17th September 2014. The report annexes contain the list of participants as well as the final agenda for the meeting.